Clinical features of liver cirrhosis patients with muscle cramping: a multicenter study. Issue 12 (December 2019) - Hiraoka, Atsushi; Yoshiji, Hitoshi; Iwasa, Motoh; Nakanishi, Hiroyuki; Karino, Yoshiyasu; Nakajima, Tomoaki; Miyaaki, Hisamitsu; Shiraki, Makoto; Kawaguchi, Takumi; Sawada, Yasuhiko; Michitaka, Kojiro; Okita, Kiwamu
Abstract : Background: There has been a small number of reports mention the clinical features including quality of life (QOL) in liver cirrhosis (LC) patients with muscle cramping and therapeutic efficacy for muscle cramping. We evaluated clinical features of muscle cramping and treatments in such patients. Patients and methods: Two-hundred and eighty-nine LC outpatients (70.6 ± 10.5 years old; male: female = 149: 140) were questioned regarding the presence or absence of muscle cramps within the last 3 months, including frequency, severity of related pain using a visual analogue scale, cramp locations, time of day, duration, sleep disturbance, daily activity decline, and being conscious of QOL decline. At the next hospital-visit, 3 or 4 months later, the subjects, who treated with medical intervention, received the same questionnaire. Results: Patients with muscle cramps (n = 160) included a higher percentage of females (53.8 vs. 41.9%, P = 0.045), worse Child–Pugh score (5: 6: 7: 8: 9: 10 = 91: 36: 15: 10: 4: 4 vs. 85: 25: 12: 5: 0: 2, P = 0.043) and lower platelet count (10.2 ± 4.7 vs. 11.8 ± 5.0 × 104/µl, P = 0.006) as compared to those without cramps (n = 129). Of the 160 with cramping, 82 (51.3%), received treatment with several types of medication, with l-carnitine the most administered drug (n = 66: 80.5%), and those also showed a tendency to complain about muscle cramps at night, sleep disturbance, reduced daily activity, and being conscious of QOL decline (each P < 0.01). We observed that frequency, visual analogue scale, sleep disturbance, daily activity, duration of muscle cramping, and being conscious of QOL decline were improved after the intervention (each P < 0.001, respectively). Conclusion: Intervention for muscle cramping improves total QOL in LC patients with such symptom.